Prevalence of psoriatic arthritis and its correlates among patients with psoriasis in Greece: results from a large retrospective study. - Papadavid, E; Katsimbri, P; Kapniari, I; Koumaki, D; Karamparpa, A; Dalamaga, M; Tzannis, K.; Βoumpas, D; Rigopoulos, D (J Eur Acad Dermatol Venereol, 2016)
OBJECTIVES: To evaluate the prevalence and its clinical characteristics of psoriatic arthritis (PsA) in a specialized psoriasis clinic of a University Hospital. METHODS: In this retrospective study, 278 patients with psoriasis were evaluated between 2011 and 2013. RESULTS: The study included 278 patients with psoriasis: 144 (52%) were male and 134 (48%) female. Their median age was 51.41 with median psoriasis presenting age of 34.52 years. Referring to the type of psoriasis, 86% presented with plaque psoriasis, 5% guttate, 2% palms and soles, 2% inverse, 1% pustular and 4% with psoriasis of more than one type. Nail disease appeared in 121 patients (43.5%) and scalp disease in 175 (63%). Of these patients, 85 (30%) had PsA, whereas 51% of patients with PsA had psoriatic nail disease. With reference to the PsA type, 43 (51%) patients presented with polyarthritis, 10 (12%) with oligoarthritis, 7 (8%) with axial arthritis, whereas the rest 25 of them (31%) had PsA of more than one type. The subgroup of patients with PsA had significantly higher rates of comorbidities including arterial hypertension, diabetes and hypercholesterolaemia compared to non-PsA patients with 41% vs. 17% (P = 0.001), 20% vs. 8% (P = 0.021) and 41% vs. 19% (P = 0.004), respectively. CONCLUSION: The prevalence of PsA among patients with psoriasis was relatively higher in Greece compared to other ethnic-based studies. Comorbidities related to life expectancy were more frequent. As there is a high percentage of undiagnosed cases with active arthritis among patients with psoriasis, dermatologists should be aware of PsA clinical signs in order to recognize it earlier and provide successful treatment.
Keywords: Adult; Arthritis, Psoriatic; Female; Greece; Humans; Male; Middle Aged; Prevalence; psoriasis